6m-3=15m

Simple and best practice solution for 6m-3=15m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6m-3=15m equation:


Simplifying
6m + -3 = 15m

Reorder the terms:
-3 + 6m = 15m

Solving
-3 + 6m = 15m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-15m' to each side of the equation.
-3 + 6m + -15m = 15m + -15m

Combine like terms: 6m + -15m = -9m
-3 + -9m = 15m + -15m

Combine like terms: 15m + -15m = 0
-3 + -9m = 0

Add '3' to each side of the equation.
-3 + 3 + -9m = 0 + 3

Combine like terms: -3 + 3 = 0
0 + -9m = 0 + 3
-9m = 0 + 3

Combine like terms: 0 + 3 = 3
-9m = 3

Divide each side by '-9'.
m = -0.3333333333

Simplifying
m = -0.3333333333

See similar equations:

| -11-6a=1a-4 | | 3/5-8(8.8) | | 8y-26=-64+2y | | 2*x^3-3*x^2-36*x+5=0 | | 2z-28=8+8z | | .07*x=84 | | 5x-12=-17 | | 11/3*-7/2*4/5-x | | 3(a-1)=-17 | | 2*x^3-2*x^2-36*x+5=0 | | 0=121p^2-100 | | m*(-4/5)=2,23 | | 4(3x+4x)-1=91 | | .5z-1=-13 | | 7-2Inx=3 | | 800x-0.55=400x+0.45 | | f(x)=9x^2+4x+9 | | 2(j-4)=10 | | 2*16+46=x | | 2*16+46= | | x^2-cx-6c^2=0 | | 5x^10-8x^7= | | .66c+6=18 | | 3x/5-2 | | 20=y/6 | | 3^2/2n4=3 | | (1-2sinx)/cosx | | 2(5x-8)=7-(5-x) | | 1-2sinx/cosx | | (3x+1)2=8 | | -18=.33x-(-9) | | x^2+676x-11840=0 |

Equations solver categories